2020
DOI: 10.1080/21505594.2020.1746557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Schu S4 aro mutants as live attenuated tularemia vaccine candidates

Abstract: There is a need for development of an effective vaccine against Francisella tularensis, as this potential bioweapon has a high mortality rate and low infectious dose when delivered via the aerosol route. Moreover, this Tier 1 agent has a history of weaponization. We engineered targeted mutations in the Type A strain F. tularensis subspecies tularensis Schu S4 in aro genes encoding critical enzymes in aromatic amino acid biosynthesis. F. tularensis Schu S4ΔaroC, Schu S4ΔaroD, and Schu S4ΔaroCΔaroD mutant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Despite the paradigm of genome reduction in pathogens leading to loss of metabolic pathway-related genes, we additionally found up-regulated genes in the pathogenic Francisella strain to be involved in biosynthesis of vitamin B7 (biotin) and other aromatic metabolites. Biotin has been shown to be required for escape from the phagosome to the cytosol ( Napier et al, 2012 ), and aroC , which is responsible for aromatic amino acid synthesis in the pathogenic Francisella strain, contributes to its intracellular growth capacity ( Cunningham et al, 2020 ). These results suggest that combined use of selective inhibitors of pathogenesis pathways together with MAIT cell antigens would be an alternative strategy for more effective vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the paradigm of genome reduction in pathogens leading to loss of metabolic pathway-related genes, we additionally found up-regulated genes in the pathogenic Francisella strain to be involved in biosynthesis of vitamin B7 (biotin) and other aromatic metabolites. Biotin has been shown to be required for escape from the phagosome to the cytosol ( Napier et al, 2012 ), and aroC , which is responsible for aromatic amino acid synthesis in the pathogenic Francisella strain, contributes to its intracellular growth capacity ( Cunningham et al, 2020 ). These results suggest that combined use of selective inhibitors of pathogenesis pathways together with MAIT cell antigens would be an alternative strategy for more effective vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is evidence to suggest that an effective live attenuated tularemia vaccine would likely need to be engineered in the Type A strain, LVS still proves a useful tool to identify targeted mutations that could be generated in the Type A background. The generation of live attenuated bacterial vaccines with defined mutations in metabolic genes has proven to be a successful strategy for vaccine development against Shigella and Salmonella Typhi, among others [54][55][56][57][58][59], and has been utilized in the generation of vaccine candidates against Ft. Several distinct metabolic mutations have been introduced into Ft to generate live attenuated, auxotrophic mutants with varying degrees of attenuation and protective efficacies [60][61][62][63][64][65][66][67][68]. Other metabolic targets for attenuation include MFS transporters such as Fpts [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…The generation of live attenuated bacterial vaccines with defined mutations in metabolic genes has proven to be a successful strategy for vaccine development against Shigella and Salmonella Typhi, among others [ 54 , 55 , 56 , 57 , 58 , 59 ], and has been utilized in the generation of vaccine candidates against Ft . Several distinct metabolic mutations have been introduced into Ft to generate live attenuated, auxotrophic mutants with varying degrees of attenuation and protective efficacies [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Other metabolic targets for attenuation include MFS transporters such as Fpts [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified the enzyme type I dehydroquinase (DHQ1, 3-dehydroquinate dehydratase, EC 4.2.1.10) as a promising target for anti-virulence drug development. The interesting features of this enzyme that have attracted our attention are: i) DHQ1 acts as a virulence factor in vivo as deletion of the aroD gene, which codes for this enzyme, has proven to afford satisfactory live oral vaccines ( Tacket et al, 1992 ; Tacket et al, 1992 ; Kärnell et al, 1993 ; Dilts et al, 2000 ; Tacket and Levine 2007 ; Malcova et al, 2009 ; Revolledo and Ferreira 2012 ; Racz et al, 2013 ; Cunningham et al, 2020 ); ii) the aroD mutation is auxotrophic, affects bacterial cell wall integrity and blocks the bacterial ability to form biofilms ( Cano et al, 2003 ; Nógrády et al, 2003 ; Sebkova et al, 2008 ); iii) DHQ1 is upregulated in small colony variants, a pathogenic form of bacteria that facilitates persistent and recurrent infections ( Proctor et al, 2006 ; Zhang et al, 2017 ); iv) no mammalian homologues of the DHQ1 enzyme have been identified; and v) DHQ1 is present in several pathogenic bacteria, including Escherichia coli, Salmonella typhi and Staphylococcus aureus . DHQ1 catalyzes the reversible dehydratation of 3-dehydroquinic acid ( 1 ) to 3-dehydroshikimic acid ( 2 ), which is the third step in the shikimic acid pathway ( Figure 1A ) ( González-Bello 2015 ).…”
Section: Introductionmentioning
confidence: 99%